Analysis of 19 STR loci reveals genetic characteristic of eastern Chinese Han population. (January 2015) - Yin, Caiyong; Ji, Qiang; Li, Kai; Mu, Haofang; Zhu, Bofeng; Yan, Jiangwei; Yu, Yanfang; Wang, Jianwen; Chen, Feng
Highlights: The 19 STR loci are highly polymorphic and informative in the studied populations. Our study reveals a distinct characteristic of 4 eastern Chinese populations. Data obtained from 19 STR loci is reflected by population migration in history.